Bacterial Photodynamic Inactivation Mediated by Methylene Blue and Red Light Is Enhanced by Synergistic Effect of Potassium Iodide - Vecchio, Daniela (Antimicrob Agents Chemother, 2015)
The inexorable increase of antibiotic resistance occurring in different bacterial species is increasing the interest in developing new antimicrobial treatments that will be equally effective against multidrug-resistant strains and will not themselves induce resistance. One of these alternatives may be photodynamic inactivation (PDI), which uses a combination of nontoxic dyes, called photosensitizers (PS), excited by harmless visible light to generate reactive oxygen species (ROS) by type 1 (radical) and type 2 (singlet oxygen) pathways. In this study, we asked whether it was possible to improve the efficacy of PDI in vitro and in vivo by addition of the inert salt potassium iodide (KI) to a commonly investigated PS, the phenothiazinium dye methylene blue (MB). By adding KI, we observed a consistent increase of red light-mediated bacterial killing of Gram-positive and Gram-negative species in vitro and in vivo. In vivo, we also observed less bacterial recurrence in wounds in the days posttreatment. The mechanism of action is probably due to formation of reactive iodine species that are produced quickly with a short lifetime. This finding may have a relevant clinical impact by reducing the risk of amputation and, in some cases, the risk of death, leading to improvement in the care of patients affected by localized infections.